Effects of selenium and sulfur treatments on nutritional quality and antioxidant substances of leaf mustard - LI Juan; ZHU Zhu-jun (浙江大学学报. 农业与生命科学版)
Effects of selenium and sulfur treatments and their interaction on the nutritional quality and antioxidant substances of leaf mustard (Brassica juncea) were studied. The results showed that the shoot dry weight was increased by 5 and 10 μmol·L-1 selenate under 0.5 mmol·L-1 sulfur supply, however, was not affected by selenate supply under 2 mmol·L-1 sulfur. The soluble sugar content was improved by adding selenium (0-5 μmol·L-1) regardless of sulfur concentration. The soluble protein and free amino acid were increased by increasing selenium (0-5 μmol·L-1) at low sulfur concentration. Selenium content in shoot was significantly increased with increasing dose of applied selenium and considerably decreased by increasing sulfur supply. Sulfur content in shoot was significantly increased with increasing dose of applied sulfur, but was not influenced by selenium concentration. The contents of P, K, Ca, Mg, Fe and Mn in shoot were not considerably affected by selenium application, but the Cu content was significantly promoted by selenium application. Increasing sulfur concentration significantly decreased the contents of Ca, Mg, Cu and Mn in shoot, but did not significantly affect the contents of P, K and Fe. Increasing appropriate dose of selenium (0-5 μmol·L-1) and sulfur significantly promoted the GSH content. Effect of selenium application on the AsA content was dependent on sulfur concentration. These results suggest that effects of selenium and sulphur supply on the antioxidant quality are important in leaf mustard.